Topical corticosteroid vehicle composition and implications for clinical practice. (27th October 2020) - Oakley, R.; Arents, B. W. M.; Lawton, S.; Danby, S.; Surber, C.
Summary: This narrative review highlights the therapeutic significance of topical corticosteroid (TCS) vehicles and provides subsequent guidance to improve clinical and research outcomes. A greater understanding of the relationship between the topical vehicle, corticosteroid and skin is needed to ensure safer, more effective treatment for patients. Topical vehicles are not inert and can affect TCS bioavailability, due to the ability of their composition to positively or negatively influence skin status and change the physiochemical characteristics of an inherent corticosteroid. However, this principle is not commonly understood, and has contributed to inconsistencies in potency classification systems. This review provides an insight into the research methods and standardization needed to determine TCS product bioavailability. It identifies formulation components responsible for vehicle composition that underpin the quality, stability, compounding and functionalities of vehicle ingredients. This helps to contextualize how topical vehicles can be responsible for clinically significant effects, and how their composition gives products unique properties. In turn, this facilitates a more in‐depth understanding of which resources offer information to inform the best selection of TCS products and why products should be prescribed by brand or manufacturer. This review will better equip clinicians and formulary teams to appraise products. It will also inform prescribing of Specials and why products should not be manipulated. The recommendations, accompanied by patient perspectives on using TCS products, assist clinical decision‐making. They also identify the need for research into concomitant application of TCS products with other topical therapies. Abstract : Click here for the corresponding questions to this CME article.